(untitled) (AACINI - International Journal of Industrial Engineering, 2023)
Organizations that have their Product Development Process (PDP) systematized are benefited because the structuring of the PDP Management brings significant advantages, since it improves the understanding of the client’s needs in the initial phases of development, facilitating costs, quality and time control. Regarding to metalworking sector, through preliminary observations and analysis, it can be concluded that many companies have non-systematized practices related to the PDP, and in cases where some degree of formalization is observed, there is no habit of register or systematize the PDP; as well as they present ignorance of PDP tools and Project Management. This reality causes companies to use resources inefficiently. In this paper, a diagnostic methodology is designed in relation to the PDP, for companies in the metalworking sector. For its elaboration, on one hand, a bibliographic survey was used in relation to PDP Management models and definitions of Maturity Levels, and on the other, the experience of the authors of this work in other productive sectors, contributing the definition of variables, sub variables and analysis categories that allow diagnosing the Maturity Level in the PDP of the companies (Basic, Intermediate and Advanced). From the analyzed bibliography, the diagnostic instrument developed by the authors was adapted to the metalworking sector. Future works will address the application of the tool in a group of metalworking companies of Litoral region.